Effects of plyometric vs. resistance training on skeletal muscle hypertrophy: A review - Jozo Grgic; Brad J. Schoenfeld; Pavle Mikulic (Elsevier, 2021)
Objective: In this review, we critically evaluate studies directly comparing the effects of plyometric vs. resistance training on skeletal muscle hypertrophy. Methods: We conducted electronic searches of PubMed/MEDLINE, Scopus, SPORTDiscus, and Web of Science to find studies that explored the effects of plyometric vs. resistance training on muscle hypertrophy. Results: Eight relevant studies were included in the review. Six studies compared the effects of plyometric vs. resistance training on muscle hypertrophy, while 2 studies explored the effects of combining plyometric and resistance training vs. isolated resistance training on acute anabolic signaling or muscle hypertrophy. Based on the results of these studies, we conclude that plyometric and resistance training may produce similar effects on whole muscle hypertrophy for the muscle groups of the lower extremities. Therefore, it seems that plyometric training has a greater potential for inducing increases in muscle size than previously thought. Despite the findings observed at the whole muscle level, the evidence for the effects of plyometric training on hypertrophy on the muscle fiber level is currently limited for drawing inferences. Compared to isolated resistance training, combining plyometric and resistance exercise does not seem to produce additive effects on anabolic signaling or muscle growth; however, this area requires future study. The limitations of the current body of evidence are that the findings are specific to (a) musculature of the lower extremities, (b) short-term training interventions that lasted up to 12 weeks, and (c) previously untrained or recreationally active participants. Conclusion: This review highlights that plyometric and resistance training interventions may produce similar effects on whole muscle hypertrophy, at least for the muscle groups of the lower extremities, in untrained and recreationally trained individuals, and over short-term (i.e., ≤12 weeks) intervention periods.